RANCANG BANGUN KALORIMETER DIGITAL BERBASIS ARDUINO UNO DENGAN SENSOR DS18B20 UNTUK PEMBELAJARAN FISIKA - Potabuga, Putri Wulandari; Amisan, Trianita Imannuela; Marianus, Marianus; Tumangkeng, Jeane Verra; Pawarangan, Ishak (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2025)
Practicum is an important component in physics learning to help students understand concepts concretely, one of which is the concept of heat and Black's principle. This research aims to design and build an Arduino Uno-based digital calorimeter prototype with a DS18B20 temperature sensor as a practicum medium that can measure temperature digitally and in real-time. The method used is Research and Development (R&D) with the stages of planning and designing tools, assembling components, and testing tool performance. The test results show that the device can measure temperature with a relative error ranging from 0.35% to 4.29% against the theoretical value based on Black's principle. The linear regression between the sensor measurement results and the theoretical value shows a coefficient of determination of =0.9789, which indicates a very high level of accuracy and data conformity. This tool not only modernises thermal experiments, but also aligns with STEM education goals through the integration of technology in the physics curriculum. This innovative device provides a practical solution for schools with limited resources and opens up opportunities for adaptation for wider educational applications.